2015
DOI: 10.1080/10888705.2015.1004407
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Epidemiological Study of Prevalence and Severity of Bit-Induced Oral Trauma in Polo Ponies and Race Horses

Abstract: Bit and bridle accessories improperly fitted in ridden horses can cause oral trauma such as bone spurs, commissure ulceration, and tongue lacerations. This study was used to identify, grade, and compare the types of oral traumas commonly found within polo ponies and race horses. Injuries were assessed visually and by palpation on the tongue, lips' commissures, and interdental space. A total of 50 polo ponies and 50 race horses were sampled in the South of England. A Poisson model was successfully fitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 14 publications
(21 reference statements)
2
43
0
Order By: Relevance
“…The bit is a potential source of considerable discomfort for the horse, as the named tissues of the mouth are extremely sensitive to mechanical stimulation. This statement is supported by clear behavioural evidence that horses find bits aversive [62,132] (see Section 5.2), as well as by convincing skeletal evidence of long-term bit-inflicted mouth injuries that would induce pain [133,134,135], features which were absent or had a much lower prevalence in feral equidae [133,134]. …”
Section: Some Implications Of Bitted and Bitless Bridle Usementioning
confidence: 92%
See 1 more Smart Citation
“…The bit is a potential source of considerable discomfort for the horse, as the named tissues of the mouth are extremely sensitive to mechanical stimulation. This statement is supported by clear behavioural evidence that horses find bits aversive [62,132] (see Section 5.2), as well as by convincing skeletal evidence of long-term bit-inflicted mouth injuries that would induce pain [133,134,135], features which were absent or had a much lower prevalence in feral equidae [133,134]. …”
Section: Some Implications Of Bitted and Bitless Bridle Usementioning
confidence: 92%
“…Use of such bits is increasingly regarded as inhumane [138], abusive [139] and, if tested in some jurisdictions, would likely be illegal (e.g., [140]). Of course, even simple bits that may be used gently, for example, the snaffle bit [36,37,131], when used inexpertly [132,135] or with malicious intent may cause significant injury and pain.…”
Section: Some Implications Of Bitted and Bitless Bridle Usementioning
confidence: 99%
“…Three postmortem studies of equid mandibles illustrate this: (1) interdental bone spurs were found in~88% of 32 working horses but there were none in 28 Przewalski horses [119]; (2) interdental space roughness was reported in 48% of 87 Warmbloods or trotters, in 25% of eight donkeys, but only in 7% of 68 zebra [108]; and (3) spurs were observed in~61% of mandibles from 66 domestic horses, but none were seen in 12 feral and Przewalski horses [7]. In addition, live assessment of oral lesions revealed that 28-30% of 50 polo ponies and 50 racehorses had interdental bone spurs, which were generally more severe in the racehorses [120]. Finally, in the first postmortem study mentioned above, the erosion of enamel and dentine of the first mandibular premolar, indicative of bit wear, was observed in 62% of 29 working horses [119].…”
Section: The Interdental Spacementioning
confidence: 98%
“…The formation of bone spurs in affected horses is apparently due to inflammation associated with repeated incidents of bit-induced bruising, laceration, and/or ulceration of the interdental gums [7,[121][122][123]. Such gum lesions reportedly occurred in 26% of 261 Trotters observed after a race [124], increased from 8% before to 31% after events in 77 competition horses [125], and were more common and severe in racehorses than polo ponies [120]. All such lesions are painful [107], and human experience would suggest that the intensity of that pain would be increased when there is further direct compressive contact between these lesions and a bit.…”
Section: The Interdental Spacementioning
confidence: 99%
See 1 more Smart Citation